A framework for setting up a country-wide network of regional surface PM2.5 sampling sites utilising a satellite-derived proxy – The COALESCE project, India. (1st August 2020) - Lekinwala, Nirav L.; Bhardwaj, Ankur; Sunder Raman, Ramya; Bhushan, Mani; Bali, Kunal; Dey, Sagnik
Abstract: Air quality management and assessment of aerosol climate effects over a large area require the strategic placement of regionally representative monitoring sites (RRMS) to capture the required information. Ground-based, fine particulate matter (PM2.5 ) concentrations measured for a long duration at high spatial resolution i.e. at several potential locations in a region help identify an optimal regionally representative site for the monitoring network. However, in the absence of long-term PM2.5 concentrations with high spatial resolution, identification of RRMS is a challenge. To identify for such situations, a novel methodology utilising satellite-derived PM2.5 is presented in this study. High spatial resolution (1 km × 1 km) daily aerosol optical depth (AOD) over several years (2004–2011) is used to derive surface PM2.5 using appropriate conversion factors. PM2.5 concentrations thus derived for a potential site and its nearby cells in the region are subjected to statistical analysis, to quantify linear/non-linear relationships between the respective PM2.5 time-series. Metrics such as coefficient of divergence (CoD), Pearson correlation coefficient (PCC) and Mutual information (MI) are calculated to assess the regional representativeness of a site. These criteria combined with physical criteria such as proximity of the site to local sources, local meteorology analysis and clustered air parcel back-trajectory analysis, are used in a weight-of-evidence approach to establish site adequacy. The selection and validation of eleven sites for the COALESCE project, is used as an illustrative example, to demonstrate the effectiveness of the site-selection methodology developed in this study. Graphical abstract: Image 1 Highlights: Novel method for identifying regional background sites for PM2.5 measurement developed. Methodology includes use of physical criteria and satellite-derived PM2.5 proxy. Satellite-derived PM2.5 using AOD and conversion factors from GEOS-Chem utilized. Sites identified using metrics such as CoD, PCC, and MI to assess homogeneity in PM2.5 . Identification of 11 regionally representative PM2.5 sampling sites for COALESCE.